Pengaruh Inovasi dan Perencanaan Strategis terhadap Kinerja Organisasi pada Wisata Edukasi Kampung Coklat Blitar - Alya Maha Devi Tahta Amrina; Gladys Greselda Gosal (Pusat Riset dan Inovasi Nasional, 2026)
In an increasingly competitive business environment, particularly within the tourism industry, an organisation's ability to innovate and design effective strategic planning has become a critical factor in sustaining and improving organisational performance. This study aims to analyse the effect of innovation and strategic planning on organisational performance at Kampung Coklat Blitar Educational Tourism. This study employed a quantitative approach, with data collected through questionnaire distribution involving 53 respondents. The sampling was conducted using a saturated sampling technique (census), in which all members of the population were used as research samples. The sampling criteria consisted of senior-level active employees with a minimum of eight years of work experience and managers at Kampung Coklat Blitar Educational Tourism. Data analysis was carried out using the SPSS software. The results of the study indicate that innovation has a positive and significant effect on organisational performance with a P-value of 0.006 and a T-statistic of 2.869. Furthermore, strategic planning also has a positive and significant effect on organisational performance with a P-value of < 0.001 and a T- statistic of 5.573.